2017
DOI: 10.5194/acp-2017-925
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantification of Methane Sources in the Athabasca Oil Sands Region of Alberta by Aircraft Mass-Balance

Abstract: Abstract. Aircraft-based measurements of methane (CH4) and other air pollutants in the Athabasca Oil 10

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
5
0
3
Order By: Relevance
“…Our findings are consistent with previous CH 4 emission studies within Canadian developments; no studies have yet identified a Canadian oil and gas producing region with emissions lower than the inventory estimate. In previous studies, factors of 1–15 have been estimated, with most being in the range of 1.5–3.0 9 11 , 14 , 15 . This implies that CH 4 abatement costs could be lower per ton of CO 2 equivalent than previously reported, due to higher volumes of CH 4 (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are consistent with previous CH 4 emission studies within Canadian developments; no studies have yet identified a Canadian oil and gas producing region with emissions lower than the inventory estimate. In previous studies, factors of 1–15 have been estimated, with most being in the range of 1.5–3.0 9 11 , 14 , 15 . This implies that CH 4 abatement costs could be lower per ton of CO 2 equivalent than previously reported, due to higher volumes of CH 4 (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that O&G CH 4 emissions may be significantly underestimated or mischaracterized (6)(7)(8)(9)(14)(15)(16)(17)(18). Ground and airborne measurement campaigns have built a clearer picture of these emissions, indicating US O&G emissions are 60% higher than in the US Environmental Protection Agency (EPA) emission inventories (9,19).…”
mentioning
confidence: 99%
“…Methane is emitted from a variety of natural and anthropogenic sources (e.g. [1,2] and references therein) and on a permolecule basis, methane is about 30 times more effective a greenhouse gas than carbon dioxide. Existing methane DIAL systems operate in the shortwave infrared (SWIR) spectral range between 1.65 and 2.3 μm, and due to low Raleigh scattering, methane profiling is possible only inside regions containing significant amounts of aerosol.…”
Section: Introductionmentioning
confidence: 99%